The temporal and embodied structure of the mineness sphere: some phenomenological ideas to frame mental health - Sánchez, Camilo Sánchez (Frontiers in Psychology, 2025)
This article highlights the import of two phenomenological variables: the implicit temporal and bodily movement experience. Then, I propose some ideas to build a framework for mental health. The proposal begins by critically considering Stanghellini’s conception of alterity, as he defines its relation through two conditions: reflexive self-awareness and “spoken word” dialogue. This conception prioritizes mental health work in the reflexive realm. In contrast, my conception prioritizes the pre-reflective realm of experience, in general, and focuses on the mineness sphere, in particular. This conception leads to consider two of Husserl’s phenomenological findings: first, awareness has a temporal structure, and second, temporal experience is constituted from the flow of consciousness. These findings are considered in terms of their constitutive import to subjectivity through the two variables. Next, I propose a general idea for a phenomenological framework of mental health work, integrating the two phenomenological variables with the concepts of alterity and ipseity. The psychotherapeutic approach known as “rhythmic relating” is considered to illustrate the key clinical role these two variables play, supporting the general aim. The conclusion presents the consequences of the proposal.